The bimodal regulation of vascular function by superoxide anion: role of endothelium - Buket, Demirci; McKeown, Pascal; Bayraktutan, Ulvi (Biochemical Society of the Republic of Korea, 2008)
Reactive oxygen species (ROS) are implicated in vascular homeostasis. This study investigated whether O2 .